Kontribusi Model Kepemimpinan dan Pengajaran Hamba Tuhan Tentang Memberi Berdasarkan 2 Korintus 9:6-15 terhadap Pengabdian Jemaat GPdI Kecamatan Loli, Kabupaten Sumba Barat - Phote, Yohanes Lende; Minggus, Minggus; Pagawak, Melkina (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
This study aims to analyze the contribution of leadership models and pastoral teaching on giving—based on 2 Corinthians 9:6–15—toward the devotion of the congregation in GPdI (Pentecostal Church in Indonesia), Loli Subdistrict, West Sumba Regency. A quantitative approach was employed using simple and multiple linear regression techniques, with data collected from 113 respondents through questionnaires. The analysis results indicate that both individually and simultaneously, the leadership model (X1) and teaching (X2) have a significant influence on congregational devotion (Y), with R² values of 0.855, 0.866, and 0.872, respectively. These findings demonstrate that 85–87% of the variance in congregational devotion is influenced by exemplary leadership and teaching on giving based on biblical principles. The study affirms that leadership and instruction rooted in love, integrity, and spiritual responsibility play a crucial role in shaping a congregation characterized by sacrificial commitment, faithful worship, and active participation in ministry. This research offers both theological and practical contributions for developing ministry strategies that are contextually relevant to the local GPdI setting.